Wood-based Columns Reinforced with Fiber-Reinforced Polymer: A Systematic Literature Review - Jardim, Pedro I. L. G.; Dos Santos, Herisson F.; Mattias, Lucas W. A.; De Araujo, Victor A. [UNESP]; Molina, Júlio C.; Christoforo, André L. (BioResources, 2025)
Fiber-reinforced polymer (FRP) is an external reinforcement solution for wooden structures, where several studies have shown its efficiency in maintenance and design. This solution is not yet among the main topics of literature, although its importance justifies new research on this relevant topic for construction. This systematic literature review involves the FRP as reinforcement in wood-based columns, using Engineering Village and Web of Science databases and PRISMA protocol to follow the procedures and ensure the quality of sampling. Reinforcement dispositions and types of assessments were identified so that the literature synthesis can contribute to identifying behavior models. Different methods of reinforcement sizing studied by the literature were synthesized and detailed as to their respective uses. A positive correlation between the reinforcement index and the increasing the load capacity of timber columns were discussed and statistically analyzed.
Keywords: Column; Fiber-reinforced polymer; Mechanical performance; Structural recovery; Structural reinforcement; Wooden construction